PEMBELAJARAN BAHASA ARAB BERBASIS MULTIMEDIA - Aliba`ul Chusna (Cendekia: Kependidikan dan Kemasyarakatan, 2012)
Abstract: Teaching Arabic language is difficult for many teachers. The Arabic teachers faces various problems while they were explaining the lesson. Mostly, these problems are caused by not understanding learners to the content of the lesson. So, the teachers should use the teaching aids or modern technological devices that help them to solve these problems significantly. Many kind of the teaching aids has made that are information and communication technology or commonly known as the multimedia. Multimedia means is one of the new technology based on computer program that can make the media more complete. It use various methods and reliable for education. Multimedia as new product from modern technology seeks to involve all the senses, including visual, hearing and feeling. And if we compared it with other educational media, multimedia are the tools and methods used to make the good communication between teachers and learners during the learning process.